Influence of Mother Tongue Interference on Senior Secondary School Students' Articulation of English Sounds in Ibadan North Local Government Area (2019)
This study investigated the influence of mother tongue (Yoruba) interference on secondary school students' articulation of English sounds in Ibadan north local government area of Oyo state. The study adopted a descriptive qualitative research design. Two public secondary schools were randomly selected in Ibadan North and five students, whose mother tongue is Yoruba and who accepted to participate in the study, were purposively selected from each school. Ten (10) purposively selected students took part in this study. English Sounds' Pronunciation Passage (ESPP) was used for data collection. Students 'pronunciations were tape-recorded and transcribed accordingly for content analysis. This was used to answer the two research questions raised. Findings, thus, revealed that students found it difficult to articulate English consonant (/z/JY\/,/d/,/0/,/v/) and vowel (73 • /,/a/,/a:/,/A/,/D ■ IJcel,/i:IJ.3 ■ /Ju:/,/S\/,/i3/,/ei/Jdtd/,/Za/,to3/,/la/) sounds correctly because of interference from their mother tongue (Yoruba). Hence, the sound system o f the students' first language (Yoruba), to a great extent, negatively influenced their articulation o f English sounds. It was, therefore, recommended, among others, that teachers should lay more emphasis on the areas o f differences in English and Yoruba sounds while teaching oral English in classes where majority o f students are Yoruba native speakers.